ANALISIS SATURASI AIR DARI METODE PERHITUNGAN SIMANDOUX DAN METODE INDONESIA LAPISAN H DILAPANGAN N - Kodoati, Virginia Judita Esterlita; Maulani, Mustamina Mustamina; Nugrahanti, Asri Asri (Petro : Jurnal Ilmiah Teknik Perminyakan, 2024)
Formation Assessment or Formation Evaluation is a science which is one of the branches of petroleum engineering that learns about the formation of rock layers or reservoirs related to their ability in hydrocarbon reserves. The research conducted for this final project is to analyze the results of air saturation from 2 methods including the Simandoux method and the Indonesian method in a field. The simandoux method is known to be generally used in formations containing shale of about 5-30%, while for the Indonesian method it is usually used for formations containing more than 30% shale. It is known that the petrophysical log analysis is carried out by looking at the petrophysical parameters of the rock in the formation. It is known that in one field it is necessary to calculate Initial in Place (GIIP) Gas in a gas field and Original Oil In Place (OOIP) in another field, to obtain the required results for water saturation values. In this study, the calculation of water saturation at well MA-01A and MA-09 was carried out and then determined the water saturation value in field N. The research was carried out using Interactive Petrophysic (IP) software. The research will be analyzed qualitative and quantitative log data. In qualitative log analysis, namely to determine formation lithology and to determine the zone where hydrocarbons are present, while the objective of quantitative log analysis is to calculate porosity, shale volume, formation temperature, water formation resistivity, and water saturation. In accordance with the research on the calculation of water saturation in the MA-01A and MA-09 well, it will be determined which method is suitable and suitable for field N. Keyword :Log Interpretation, Water Saturation, Well log, Indonesia Method, Simandoux Method